Innovations in Bioactive Materials for Dental Pulp Vitality Preservation in Children and Adolescents - Purva K. Desai; Shreya M. Hiwalkar; Hyun-Joo Kim; Jonghyun Shin; Hyo-Seol Lee; Ho-Wook Jun; Kyounga Cheon (Applied Sciences)
Preserving dental pulp vitality is crucial in pediatric and adolescent dentistry to promote long-term oral health and reduce the need for invasive procedures. Vital pulp therapy (VPT) enhances pulp healing and dentin formation through advanced pulp capping materials. While calcium hydroxide-based materials laid the foundation for VPT, calcium silicate-based materials like mineral trioxide aggregate, Biodentine, and TheraCal offer superior biocompatibility and sealing properties. Recent advancements focus on regenerative strategies that enhance biocompatibility, antibacterial efficacy, and anti-inflammatory effects. Tissue engineering approaches, including stem cells, growth factors, and peptide-based scaffolds, are being explored to improve pulp regeneration and long-term treatment success. This review highlights recent developments in VPT for pediatric and adolescent patients, emphasizing minimally invasive techniques, clinical challenges, and the potential of emerging biomaterials. Continued research into biomaterial efficacy and regenerative capabilities holds promise for advancing VPT, ensuring more effective and biologically driven treatment strategies for young patients.